Miejsce ekfrazy w bizantynistycznej historiografii artystycznej - Małgorzata Smorąg Różycka (Vox Patrum, 2018)
In Byzantium, writing ekphrases was one of the standard literary skills, developed during school instruction. Yet, in Byzantine art history, the analysis of Byzantine ekphrases had long been beyond the scope of researchers who favoured rather the iconographic and formal comparative methods. It was not until the discovery of the role of rhetoric in the shaping of pictorial formulae and iconographic programmes of paintings, by H. Maguire, that the importance of ekphrases was fully recognised – especially as far as interpretation of the contents of art works and the understanding of mechanisms governing the development of iconographic and compositional programmes that ‘defied’ the canon were concerned. The examples of ‘reversed’ compositional schemes in the Christ’s Entry into Jerusalem scene in the Church of the Virgin at Daphni or the Holy Myrrhbearers at the Sepulchre in the Mileševa Monastery, discussed in the present paper, considered within a broad context of architectural space and the liturgy, have demonstrated that the Byzantine artist was able to freely shape his pictorial formulae while looking for new ways of visualising dogmatic content, especially in the period after the Iconoclastic Controversy (726-843). An example of Michael Psellos’ ekphrasis of an image of the Crucifixion further proves that also Byzantine writers were faced with a similar problem of finding adequate forms for expressing dogmatic content in keeping with the literary canon. In his description of the image, Psellos not only identified its particular elements (schemata) but also referred to the experience and knowledge of the recipient who was supposed to be able to discern in the picture also the reality that could not be represented using artistic means. Thus, the above affinity between the artistic and literary stances seems to release the researchers of Byzantine art from strict adherence to stereotypical interpretations in keeping with the methodological canon.